2011
DOI: 10.1021/cb200155t
|View full text |Cite
|
Sign up to set email alerts
|

A Map of Minor Groove Shape and Electrostatic Potential from Hydroxyl Radical Cleavage Patterns of DNA

Abstract: DNA shape variation and the associated variation in minor groove electrostatic potential are widely exploited by proteins for DNA recognition. Here we show that the hydroxyl radical cleavage pattern is a quantitative measure of DNA backbone solvent accessibility, minor groove width, and minor groove electrostatic potential, at single nucleotide resolution. We introduce maps of DNA shape and electrostatic potential as tools for understanding how proteins recognize binding sites in a genome. These maps reveal pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 40 publications
4
96
0
Order By: Relevance
“…Earlier reports have shown that the phosphodiester backbone at purine-pyrimidine (RpY) dinucleotides, which intrinsically widen the minor groove, are cleaved by DNase I at higher rates (32,33). Having a widened minor groove where the backbone is cleaved would thus seem to be beneficial (34).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier reports have shown that the phosphodiester backbone at purine-pyrimidine (RpY) dinucleotides, which intrinsically widen the minor groove, are cleaved by DNase I at higher rates (32,33). Having a widened minor groove where the backbone is cleaved would thus seem to be beneficial (34).…”
Section: Resultsmentioning
confidence: 99%
“…CBR associations with Crx −/− up-or down-regulated genes were taken from Corbo et al (18). Minor groove width was predicted at base pair resolution using the ORChID2 program (28), and ORChID2 scores were summed across all base pairs in each CRE or Crx motif to give a total sequence minor groove width score. CpG island annotations were obtained from the UCSC Genome Browser at http://genome.ucsc.edu/index.html (39).…”
Section: Methodsmentioning
confidence: 99%
“…High GC content is associated with several distinct features that can affect the cis-regulatory potential of a sequence (4, 23), including high nucleosome occupancy (24-26) and a wide DNA minor groove (27,28). In some cases, TF binding is promoted by high nucleosome occupancy (29), and minor groove width can affect the binding specificity of homeodomain TFs (12).…”
Section: High Local Gc Content Distinguishes Functional Crx Sites Frommentioning
confidence: 99%
“…Two primary sequence features (PSFs) (GC content and minor groove width as estimated by ORChID2 [Rohs et al 2009;Bishop et al 2011] score) and six chromatin features (The ENCODE Project Consortium 2012; Hoffman et al 2013) (DNase I HS from Duke; DNase I HS from University of Washington [UW]; FAIRE-seq; and ChIP-seq of H3K4me1, H3K36me3, and RNA polymerase POLR2A) are significantly enriched in sequences that drive high expression in our assay (Wilcoxon rank sum test, P < 0.05 Bonferroni correction with N = 16) (Supplemental Table 2). We used these data to develop a quantitative model that distinguishes active CREs from inactive CREs.…”
Section: Sequence and Chromatin Featuresmentioning
confidence: 99%
“…ucsc.edu/goldenPath/hg19/encodeDCC/wgEncodeRegTfbsClustered/. GC-content and ORChID2 (Rohs et al 2009;Bishop et al 2011) scores were calculated from the nucleotide sequences of the CREs.…”
Section: à4mentioning
confidence: 99%